Bakti sosial pemeriksaan, pengobatan skabies dan pendampingan pimpinan dan perangkat di pondok pesantren Kabupaten Prabumulih - Rusmawardiana; Nopriyati, Nopriyati; Argentina, Fifa; Deddy, Deddy; Antonius, Cayadi Sidarta; Setiawan, Ivon; Veronica, Veronica (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Scabies is a skin disease caused by infestation and sensitization of Sarcoptes scabiei var. hominis. The prevalence of scabies reaches more than 20% in developing countries and mainly affects children. Scabies is more commonly found in a location with dense population, with high direct or indirect contact, such as in Islamic boarding schools. This counseling and community service activity aims to provide information related to scabies to students and to screen scabies risk factors at Darussalam Prabumulih Islamic Boarding School. The results of the questionnaire screening showed that respondents had a high risk of scabies infestation based on an assessment of the 4 main risk factors. The results of anamnesis and physical examination of 49 students showed that 19 students (38.7%) had scabies infestation and 30 students (61.3%) were free from scabies infestation. This counseling is expected to help reduce the number of scabies infestations in densely populated residential locations, especially in Islamic boarding schools.